EKSPLORASI ETNOMATEMATIKA PADA MASJID AL-ALAM CILINCING - Mardiyati, Ana Putri; Al Hasyir, Muhammad Izdad; Khotimah, Silvia Khusnul; Mulyatna, Fauzi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Mathematics and culture are two things that are closely related to people's lives. Ethnomathematics can be an approach to learning mathematics to make it easier for students to understand mathematical concepts. Historical buildings can be objects for observing mathematical concepts. Al-Alam Mosque is one of the historic buildings in Jakarta which was built in 1520 AD. The Al-Alam Mosque was built by Sultan Fatahillah with the aim of spreading Islam as well as being a witness to the Portuguese liberation event from Sunda Kelapa. This research uses qualitative methods with an ethnographic approach. The data collection techniques used were observation, interviews and documentation. The ethnomathematics exploration of the Al-Alam Mosque that was studied was the geometric concept of the mosque building. In mosque buildings, mathematical concepts are found, which include flat shapes, spatial shapes, angular shapes and symmetrical shapes. This is an alternative solution to increase students' interest in studying mathematics by linking history and culture in everyday life